Antimalarial Activity of Sea Sponge Extract of Stylissa massa originating from waters of Rote Island - Jefry Presson; Respati Tri Swasono; Sabirin Matsjeh; Meta Permata Putri; Zulfah Az Zahra; Lukas Pardosi (Jurnal Kimia Sains dan Aplikasi, 2021)
Research on the isolation, toxicity test, antimalarial test, and identification of the active compound from the ethyl acetate fraction of Stylissa massa sponge from Oenggae waters, Rote Island, has been conducted. This study aimed to investigate the antimalarial activity of the ethyl acetate fraction of the Stylissa massa sponge. Isolation was carried out by the extraction method using a mixed solvent of methanol: dichloromethane of 3: 2 (v/v), then the extract was partitioned in a solvent mixture of ethyl acetate: water of 1: 2 (v/v). The ethyl acetate extract obtained was separated by column chromatography using the gradient polarity system method. The toxicity test of each fraction was carried out by the Brine Shrimp Lethality Test (BSLT) method, and the antimalarial test was carried out by the haematin polymerization inhibition method. Identification of compounds from the active fraction in the antimalarial test was carried out using Liquid Chromatography-Mass Spectrometry (LC-MS). The extraction yield was 1.14 g (0.23%) of the ethyl acetate extract in the form of a dark brownish-yellow oily solid. Separation by column chromatography resulted in 15 fractions. Toxicity test results showed the four most active fractions with LC50 values, which are very promising for new drug discovery. The IC50 value in the antimalarial activity test of the four fractions indicated that the Stylissa massa sponge ethyl acetate extract was more active than the standard chloroquine compound (115 μg/mL). The LC-MS analysis indicates that fraction 11 contains two compounds that have been reported, and 1 compound is unknown. In contrast, fraction 14 indicates that it contains three compounds that have been reported and one unknown compound.